Evaluasi Pertumbuhan Semai Beberapa Provenan Sungkai (Peronema Canescens Jack) di Kalimantan Selatan - Gusti Muhammad Hatta (Fakultas Kehutanan Universitas Gadjah Mada, 2008)
Growth Evaluation of Several Provenances of Sungkai (Peronema Canescens Jack) Seedlings in South KalimantanSungkai (Peronema canescens Jack) is among the species recommended for industrial forest plantation (IFP) by the Ministry of Forestry. Despite this fact, very little is known about the extent of genetic variation in wild populations and few attempts, if any, have been made at genetic improvement. Sungkai cuttings are collected wherever available, rather than companies seeking high-quality stockplants. No effort has been made to increase the quality of cuttings by collecting them from different geographical origins (provenance test). Cuttings from five provenances in South Kalimantan were tested at nursery stage in order to indent6 the best provenance. The result showed that all provenance had a 100% survival rate. Kandangan provenance was the fastest in finishing shoots formation. There is no significant difference in term of shoot length however, in average, provenances from Tambarangan and Tanjung had longer shoots, i.e. 31 cm and 30.65 cm, respectively.